Food literacy competencies: A conceptual framework for youth transitioning to adulthood. (30th August 2018) - Slater, Joyce; Falkenberg, Thomas; Rutherford, Jessica; Colatruglio, Sarah
Abstract: Objective : The modern foodscape has changed dramatically in recent decades in terms of where, what, how and with whom we eat. This has been facilitated by a transition from traditional, healthy and basic foods prepared in the home to ultraprocessed, unhealthy foods requiring little planning and preparation prior to consuming. Consequently, many youth lack the food literacy (knowledge, skills and critical perspectives) necessary to be well and minimize their risk of obesity and chronic diseases, in the context of a complex food system. The specific dimensions of these knowledge, skills and dispositions, however, are unknown. This study identified critical food literacy competencies required by youth as they transition to independent adulthood.Design : This study employed a Delphi methodology to achieve consensus statements on critical food literacy competencies within a framework encompassing cognitive, psychomotor and affective dimensions.Participants : A panel of 41 experts including dietitians, teachers and college/university students participated in in‐depth interviews.Analysis : Results were thematically analysed and incorporated into two subsequent surveys completed by panel members. Rater agreement was set at 75% agreeing/strongly agreeing with survey items. A panel subgroup further delineated results into competency statements.Results : Within the themes of "confidence and empowerment, " "joy and meaning" and "sustainable and equitable food systems, " 16 broad competency areas, and 59 specific competencies were identified. These were assembled into a Food Literacy Framework.Conclusion : Results can be used to support food and nutrition education in community settings as well as the formal school system, and to advocate for resources to support food literacy education programmes.